Effectiveness of Health Education on Self-Care Management of Hypertension Patients in the Working Area of Medan Johor Primary Health Center, 2025 - Aspiati Aspiati; Ristika Julianty Singarimbun (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Background and Purpose: Hypertension remains a leading non-communicable disease burden globally, with self-care management identified as a critical determinant of blood pressure control and complication prevention. Despite efforts to increase treatment coverage, adherence to self-care behaviors among hypertensive patients in primary health center settings in Indonesia remains suboptimal. This study aimed to evaluate the effectiveness of structured health education interventions on improving self-care management among hypertension patients registered at Medan Johor Primary Health Center. Methods: A quasi-experimental study with a one-group pre-test–post-test design was conducted from September to December 2025. A purposive sample of 60 hypertension patients meeting the inclusion criteria was recruited. The intervention comprised four structured health education sessions delivered over four consecutive weeks. Self-care management was measured using the adapted Hypertension Self-Care Activity Level Effects (H-SCALE) instrument across six domains. Ethical clearance was obtained from the Research Ethics Committee of Universitas Bunda Thamrin (No. 042/EC/UBT/2025). Data were analyzed using the Wilcoxon Signed-Rank Test (α = 0.05). Results: The mean total self-care score increased significantly from 50.4 ± 8.5 (pre-test) to 74.4 ± 6.3 (post-test). All six self-care domains demonstrated statistically significant improvements (all p < 0.001). The overall Wilcoxon Signed-Rank Test yielded Z = −6.842, p < 0.001, with a large effect size (r = 0.88). Blood pressure monitoring showed the greatest improvement (Δ = 25.2), followed by dietary management (Δ = 25.0). Conclusion: Structured health education is highly effective in improving self-care management across all domains among hypertensive patients at the primary health center level. Integration of routine health education programs within hypertension management protocols at Puskesmas is strongly recommended to optimize patient outcomes and reduce long-term cardiovascular complications.